2018
DOI: 10.1002/adsc.201800728
|View full text |Cite
|
Sign up to set email alerts
|

Diversity‐Oriented Synthesis of Functionalized Imidazopyridine Analogues with Anti‐Cancer Activity through a Transition‐Metal Free, One‐pot Cascade Reaction

Abstract: A transition-metal free, high yielding and efficient three-component reaction was designed and incorporated into two sequential oxidation and cyclization reaction cascades in one-pot with the assistance of microwave irradiation. A chemical collection of functionalized 3-substituted imidazopyridines was prepared by means of the mild reaction and simple operational procedure. The reaction has a broad tolerance for a variety of substituted carbonyl aldehydes, anilines and 2phenyl-imidazo[1,2-a]pyridines. Screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Compound 9i Inhibits Cervical Cancer Cell Viability in a Time-and Concentration-Dependent Manner. Our previous study found that a series of novel imidazopyridine analogues have anticancer activity in various tumor cell lines [6]. We want to further explore the molecular mechanism of the anticancer effect of these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 9i Inhibits Cervical Cancer Cell Viability in a Time-and Concentration-Dependent Manner. Our previous study found that a series of novel imidazopyridine analogues have anticancer activity in various tumor cell lines [6]. We want to further explore the molecular mechanism of the anticancer effect of these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Small molecular compound 9i was synthesized by the chemical synthesis lab of IATTI as previously described [ 6 ]. Other regular chemical reagents were purchased from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Moreover, it can facilitate the formation of pharmaceutical and bioactive scaffolds 2 and versatile intermediates in organic synthesis 3 and provide access to natural products 4 under sustainable reaction conditions. The construction of these motifs has drawn considerable attention for use in different reactions, including intermolecular–intramolecular cascade cyclization, 5 ring expansion/contraction, 6 transition-metal/metal-free catalysis, 7 and radical chemistry. 8 However, most of these preparative methods involve the multistep synthesis of starting precursors, generation of toxic waste, low atom economy, and harsh reaction conditions, limiting their applicability in synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advancement has been made to modify the C‐3 position of imidazo[1,2‐ a ]pyridine using alkylation, thiocyanation, nucleophilic addition,, arylation or alkenylation, fluorination, and acetylation . However, aminomethylation at the C‐3 position of imidazo[1,2‐ a ]pyridine is rare with only two reports in the literature , .…”
Section: Introductionmentioning
confidence: 99%